Energy scale of dielectric coupling in antiferromagnetic insulators. (1st October 2022) - Zhang, Jiarui; Chen, Cai; Xiang, Shuqing; Zhang, Junchao; Qi, Qi; Huang, Rui; Yu, Yang; Chen, Kai; Han, Zhida; Yuan, Guoliang; Liu, Junming; Zhu, Jinsong
Abstract: To probe the energy of dielectric coupling between the dipole chains and the quasipolarons based on extension of the polaron concept, dielectric and magnetic properties of antiferromagnetic insulators, namely Ca4-x Cux Ti4 O12 (x = 3, 2 and 1), are investigated at different temperatures. The energy is estimated larger than 56 meV of the dipole interaction energy, but smaller than 88 meV of the dipole-chain thermal activation energy which is for the Dissado-Hill type dielectric relaxation. In particular, the quasipolaron ingredient is at least 28 meV of the total superexchange interaction which bond one singe titanium ion of the dipole chain with four quasipolarons. Then, the energy of the coupling is in the range from 84 meV to 88 meV. The experimental observation, suggests the dielectric coupling may provide an approach to obtain large permittivity in strongly-correlating systems of antiferromagnetic insulators.